Ageing and contemporary female musicians - Gardner, Abigail (Routledge, London ; New York : Routledge, 2019)
Ageing and Contemporary Female Musicians focuses on ageing within contemporary popular music. It argues that context, genres, memoirs, racial politics and place all contribute to how women are 'aged' in popular music. Framing contemporary female musicians as canonical grandmothers, Rude Girls, neo-Afrofuturist and memoirists settling accounts, the book gives us some respite from a decline or denial narrative and introduces a dynamism into ageing. Female rock memoirs are age-appropriate survival stories that reframe the histories of punk and independent rock music. Old age has a functional and canonical place' in the work of Shirley Collins and Calypso Rose. Janelle Mone, Christine and the Queens and Anohni perform queer' age, specifically a kind of going beyond' both corporeal and temporal borders. Genres age, and the book introduces the idea of the time-crunch; an encounter between an embodied, represented age and a genre-age, which is, itself, produced through historicity and aesthetics. Lastly the book goes behind the scenes to draw on interviews and questionnaires with 19 women involved in the contemporary British and American popular music industry; DIY and ex-musicians, producers, music publishers, music journalists and audio engineers. Ageing and Contemporary Female Musicians is a vital intergenerational feminist viewpoint for researchers and students in gender studies, popular music, popular culture, media studies, cultural studies and ageing studies.
OCLC-licensed vendor bibliographic record.
Keywords: Women musicians; Older musicians; Women in music; Aging -- Social aspects; Popular music -- Social aspects; SOCIAL SCIENCE / Gender Studies